Exploring the relationship between writing apprehension and writing performance: a qualitative study - Badrasawi, Kamal J I; Zubairi, Ainol Madziah; Idrus, Faizah (Canadian Center of Science and Education, 2016)
Writing skill is seen as a cornerstone of university students’ success in both academic and career life. This qualitative study was conducted to further explore the teachers’ and students’ perceptions on the relationship between writing apprehension and writing performance, contributing factors of writing apprehension, and strategies to reduce writing apprehension. Semi-structured interviews were conducted to get more in-depth information from two respondents: one experienced instructor of teaching writing at the Centre for Languages and Pre-University Academic Development (CELPAD), International Islamic University Malaysia, and another, a graduate student who was reported to having a high level of writing apprehension using Daly and Miller’s (1975) questionnaire on writing apprehension. Thematic analysis approach was used for data analysis. Both respondents were convinced that writing apprehension has a negative influence on students’ writing performance; the sources of contributing factors could be students, instructors, and teaching learning setting; and writing apprehension could be reduced through suggested strategies. It is recommended that instructors should be more aware of students’ problems in the writing skill.